An Inquiry Model for Mathematics Teachers’ Professional Development - Nam, Nguyen Danh (VNU Journal of Science: Education Research; Vol 32 No 4, 2016)
Abstract: This paper proposes an inquiry model for improving the teaching of mathematics based on the practice of lesson study. This model provides both pre-service and in-service mathematics teachers with multiple pathways for designing a mathematics lesson plan. The result of this research plays an important role in determining if the model is effective in helping teachers to develop their professional expertise. The model also leads to teachers’ improved teaching and provides valuable insights into the process of mathematics teaching. Keywords: Professional development, lesson study, teaching Mathematics, research lesson.